PARTISIPASI GOVERNANCE DALAM PEMBERDAYAAN PELAKU USAHA KECIL DAN MENENGAH DI KECAMATAN PASANGKAYU KABUPATEN MAMUJU UTARA - Mutmainna Mutmainna; Burhanuddin Burhanuddin; Nasrulhaq Nasrulhaq (Kolaborasi : Jurnal Administrasi Publik, 2018)
This study aimed to determine the participation of governance in empowering small and medium business actors in Pasangkayu District, North Mamuju Regency. The type of research was qualitative. The type of research was phenomenology. Data collection techniques were such as interview, observation, and documents. The result of this research was that participation in decision making had not been optimal because the training schedule was still limited. Participation in implementation, participation in benefid taking and participation in evaluation had not been maximized because there were still many communities receiving SME assistance that was not as expected. Internal factors ie human resources were running well because it could help people’s lives. External factors were such as facilities and infrastructure had not been realized because the SME assistance tool provided by the Office Koperindag misused by the community. Keywords: Participation, governance, SME empowerment